Comparison of Misconception of Heart Attack Pain with Heart Burn How Common Is It - Pervez , Noman; Muhammad Afzal; Fazal Ur Rehman; Khan, Abdul Ghaffar; Muhammad Hashim; Syed Abdul Bari; Kumar, Rawindar; kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: The public often misunderstands the difference between a heart attack (myocardial infarction, MI) and heartburn. Heartburn, which is frequently brought on by acid reflux, commonly manifests as a burning ache in the chest, whereas myocardial infarction is characterized by sudden chest discomfort and additional symptoms like palpitations. Particularly among those with limited healthcare literacy, confusion between these two disorders can result in misdiagnosis, increased health risks, and delayed treatment. Methods: At a tertiary care hospital in Quetta, 200 volunteers from various socioeconomic levels (upper, middle, and lower) were enrolled in a cross-sectional descriptive study. The study gathered information on symptom interpretation, healthcare-seeking behaviour, and associated characteristics such belching, nausea, and the location of chest pain through semi-structured interviews and self-administered questionnaires. Thematic analysis was used to examine the data. Results: The findings showed that a considerable number of people confused MI pain for heartburn, with those from lower socioeconomic classes being most affected (50.5%). Symptoms that were frequently misconstrued included nausea (17.5%), chest discomfort (22%), and epigastric pain (36%). On the other hand, the most often identified MI symptoms were shortness of breath (24.5%) and chest discomfort (28%). Conclusion: In conclusion, many people confuse heart attacks with heartburn, particularly those from lower socioeconomic backgrounds who have less access to healthcare and less literacy. To improve early identification of myocardial infarction and lower health problems, this study emphasizes the significance of enhancing public awareness and health education.